2005
DOI: 10.1055/s-2005-858071
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Anaesthesia of the Axillary Brachial plexus: Efficacy of Multiple Injection Approach

Abstract: Performing axillary nerve blockade using ultrasound guidance provides excellent anaesthesia and fast onset times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 15 publications
0
23
0
2
Order By: Relevance
“…Schwemmer et al 15 reported complete anesthesia of the brachial plexus with fast onset following ultrasound guided axillary block in 46 patients. Among published comparative studies to date, most were small scaled, and failed to show improved block success with ultrasound based on assessment of surgical anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Schwemmer et al 15 reported complete anesthesia of the brachial plexus with fast onset following ultrasound guided axillary block in 46 patients. Among published comparative studies to date, most were small scaled, and failed to show improved block success with ultrasound based on assessment of surgical anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Schwemmer et al [15,16] stated that ultrasonography application significantly increases the success rate of axillary blocks and that starting time of operation following the block is much earlier. Throughout our study, we detected that sensory block started earlier in the ultrasonography-applied group although this was not singnificant statistically and on the other hand, that motor block rate in this group was significantly higher in comparison with the other group.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative study by Casati et al [12] however, could not demonstrate this improved success rate. Benefits of the use of ultrasound are the reduced need for nerve stimulation with improved patient comfort [12], reduced volume of local anesthetics used [1316], and shortened onset time [10, 17]. In this retrospective study focussing on learning of the skills, we found that ultrasound-guided axillary brachial plexus block when performed by junior residents is learned faster and with a higher success rate compared to nerve stimulator-guided axillary brachial plexus blocks.…”
Section: Discussionmentioning
confidence: 99%